Displacement analysis of asymmetrically loaded cable - Juozapaitis, Algirdas; Norkus, Arnoldas (Journal of Civil Engineering and Management, 2004)
A deformed state of parabolic shape suspension cable subjected to asymmetric loading is under consideration. The cable kinematic nature of vertical and horizontal displacements, resulted from complementary asymmetrically distributed load are investigated, the expressions for their maximum values are derived. The deformability of suspension cable versus its curvature increment is investigated. The possibilities to stabilise the primary parabolic shape of suspension cable subjected to an asymmetric load are examined. Numerical simulation results are presented. First Published Online: 14 Oct 2010